An Improved Question Format for Measuring Conspiracy Beliefs. Issue 4 (30th January 2020) - Clifford, Scott; Kim, Yongkwang; Sullivan, Brian W
Abstract : In an era of increasing partisan polarization and media fragmentation, interest in the causes of conspiracy beliefs has been growing rapidly. However, there is little consensus on how to measure these beliefs. Researchers typically present respondents with a conspiratorial statement, then assess their endorsement of the statement using an agree-disagree scale, a true-false scale, or some other variant. Researchers sometimes include a no-opinion response option and sometimes do not. Yet, there is little evidence as to the best format. In this article, we argue that common measures not only are challenging for respondents to answer, but also inflate estimates of conspiracy belief among the mass public. We introduce an alternative measure that presents respondents with an explicit choice between a conspiratorial and a conventional explanation for an event. Across three studies, the explicit choice format reduces no-opinion responding and reduces estimates of conspiracy belief, particularly among those low in political knowledge or cognitive reflection. These results suggest that previous findings may be inflated due to measurement artifacts. This evidence suggests that researchers adopt the explicit choice format for measuring conspiracy beliefs and provide a no-opinion response option.